Outrage : the rise of religious offence in contemporary South Asia - Rollier, Paul; Frøystad, Kathinka, 1966-; Ruud, Arild Engelsen (UCL Press, 2019)
Outrage: The Rise of Political Offence in Contemporary South Asia analyses the sharp rise in blasphemy accusations in South Asia.